ANALYSIS OF TEACHER STRATEGIC MANAGEMENT IN IMPROVING THE QUALITY OF LEARNING ARABIC - Intan Afriati (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Strategic management by teachers plays a role in improving the quality of Arabic language learning. It explores various strategies that can be implemented to optimize the learning process, including curriculum planning, teaching methods, and assessment. Case studies or concrete examples that show the positive impact of strategic management on student learning outcomes in Arabic have also been widely discussed in research results in several articles or journals. The type of research used in this discussion is using literature study which includes: systematic identification, analysis of documents containing information related to the study problem. The research results show that 1). The application of effective strategic management, such as careful planning and the use of innovative teaching methods, can improve the quality of teaching. Teachers who implement well-planned strategies tend to be better able to convey material in a clear and interesting way, which has a positive impact on student understanding. 2). Strategic management involving interactive and participatory learning methods can increase student engagement. Research shows that students who actively participate in learning tend to have greater motivation and interest in Arabic. 3). Strategic management encourages positive changes in teaching practices, such as the adoption of new technologies, more effective teaching methods, and more student-centered approaches, thereby improving student learning outcomes.